2019
DOI: 10.3390/ijerph16101683
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Occurrence and Human Health Risk in Drinking Water Wells from Southern Edge of Chinese Loess Plateau

Abstract: Fluoride hydrogeochemistry and associated human health risks implications are investigated in several aquifers along the southern edge of the Chinese Loess Plateau. Locally, 64% shallow groundwater samples in loess aquifer exceed the fluoride limit (1.5 mg/L) with the maximum of 3.8 mg/L. Presently, the shallow groundwater is the main source of private wells for domestic use, and this is clearly a potential risk for human health. Hydrogeochemistry and stable isotopes are used to elucidate the diversity of occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 49 publications
2
20
0
Order By: Relevance
“…The parameters of the semivariogram model used to map and predict the content of various PTEs in the soil based on the ordinary kriging method are shown in Table 5 . The percentage of the nugget value C 0 to the base station value (C 0 + C) is the nugget ratio (C 0 /(C 0 + C)), which is generally used as a measure of the degree of the spatial correlation of variables [ 48 ]. If the nugget ratio is less than 0.25, the spatial correlation degree of the variable is strong, if the nugget ratio is between 0.25 and 0.75, the variable spatial correlation degree is medium, and if the ratio is greater than 0.75, the spatial correlation degree is weaker [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The parameters of the semivariogram model used to map and predict the content of various PTEs in the soil based on the ordinary kriging method are shown in Table 5 . The percentage of the nugget value C 0 to the base station value (C 0 + C) is the nugget ratio (C 0 /(C 0 + C)), which is generally used as a measure of the degree of the spatial correlation of variables [ 48 ]. If the nugget ratio is less than 0.25, the spatial correlation degree of the variable is strong, if the nugget ratio is between 0.25 and 0.75, the variable spatial correlation degree is medium, and if the ratio is greater than 0.75, the spatial correlation degree is weaker [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…MgCl2•6H2O, FeSO4•7H2O and Ce(SO4)2•4H2O were dissolved for the mixed solution with a molar concentration ratio of Mg:Fe:Ce of 4 To choose the best synthetic method for the adsorbent, two synthesis methods (i.e., the co-precipitation method and hydrothermal synthesis method) were compared. The detailed co-precipitation method was (1) preparing the required experimental solution, (2) adjusting pH with 6 mol•L −1 NaOH to 8.5 and keeping this pH more than 30 min, (3) keeping still for more than 24 h, (4) washing the acquired precipitate and centrifuging all the mixed solution-including precipitate and washing water, (5) drying the precipitate under 65 • C for 24 h, and (6) calcining in the muffle furnace at 600 • C. The detailed hydrothermal synthesis method was (1) preparing the required experimental solution, (2) adding the solution and 6mol•L −1 NaOH to the autoclave and fastening the gap, (3) heating for 6 h under 90 • C, (4) sampling after cooling and exhausting, (5) washing the acquired precipitate and centrifuging all the mixed solution-including precipitate and washing water, (6) washing and drying the precipitate under 65 • C, and (7) calcining in the muffle furnace at 600 • C.…”
Section: Optimization and Preparation Of The Adsorbentmentioning
confidence: 99%
“…Drinking water safety and sustainability, closely bound with people's lives, have always attracted the most public attention among various the human health-related issues. Fluoride pollution is one of the most common challenges in drinking water safety, and excessive fluoride intake can affect the human body and lead to severe health problems, such as fluorosis and osteoporosis [1][2][3]. It was reported that about 200 million people in 25 countries around the world are under the threat of the fluorosis [4].…”
Section: Introductionmentioning
confidence: 99%
“…Major anthropogenic processes [Figure 1S] include climate change, irrigation of dry land without sufficient drainage, increase in the use of phosphate fertilizer, animal manures, domestic and industrial wastewater discharge on the surface, automobile exhaust increase the fluoride contamination in groundwater (Genxu and Guodong 2001). Fluoride's effects on human health, however, are not immediate but chronic, so long-term exposures to high doses of fluoride are obligatory (Jia et al 2019). The key routes of human ingestion of fluoride are fluoride-containing groundwater used for drinking purposes, food compounds, and toothpaste (Das et al 2020).…”
Section: Introductionmentioning
confidence: 99%